2019
DOI: 10.1016/j.neuron.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Inflaming the Brain

Abstract: Proteomic analysis of Zika virus infected primary human fetal neural progenitors suggests a role for doublecortin in the pathological consequences of infection in the cortex. Front. Microbiol. 9, 1067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Fibrinogen is an important part of the coagulation cascade and can enter and deposit in the brain following vascular injury or compromise of the blood-brain-barrier. It has been recently shown to have a pleotropic role in the CNS including activation of inflammation, induction of scar formation, promotion of cognitive decline and inhibition of repair [20,21]. Mitochondrial import membrane translocases have an implied role in several neurological disease conditions [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is an important part of the coagulation cascade and can enter and deposit in the brain following vascular injury or compromise of the blood-brain-barrier. It has been recently shown to have a pleotropic role in the CNS including activation of inflammation, induction of scar formation, promotion of cognitive decline and inhibition of repair [20,21]. Mitochondrial import membrane translocases have an implied role in several neurological disease conditions [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is an important part of the coagulation cascade and can enter and deposit in the brain following vascular injury or compromise of the blood-brain-barrier. It has been recently shown to have a pleotropic role in the CNS including activation of in ammation, induction of scar formation, promotion of cognitive decline and inhibition of repair (20,21). Mitochondrial import membrane translocases have an implied role in several neurological disease conditions (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Additionally, blood-derived fibrin acts on CD11b/CD18 of microglia, causing damage to synapses and also causing cognitive impairment. 32 Belfiore, R. et al evaluated female 3xTg-AD and nontransgenic (NonTg) mouse models and found that the Aβ load and Tau protein caused by Aβ deposition are located at Thr212/Ser214 or Ser202/Thr205 and Ser422. The phosphorylation of Tau protein leads to a neuroinflammatory response, which can also lead to a gradual decline in cognitive function.…”
Section: The Influence Mechanism Of Microglia On Cognitive Functionmentioning
confidence: 99%
“…The lack or downregulation of the receptors SIRPα and CB1 on microglia and the receptor CD2000 on neurons will lead to microglia, and phagocytosis‐mediated increases in synapse loss and cognitive impairment 29–31 . Additionally, blood‐derived fibrin acts on CD11b/CD18 of microglia, causing damage to synapses and also causing cognitive impairment 32 …”
Section: Ad and Microgliamentioning
confidence: 99%
See 1 more Smart Citation